2012
DOI: 10.2174/1874306401206010020
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Gender, and Ethnic Variations Alter the Clinical Implications of the Epworth Sleepiness Scale in Patients with Suspected Obstructive Sleep Apnea

Abstract: Introduction:The Epworth Sleepiness Scale (ESS) is often used in the evaluation of obstructive sleep apnea (OSA), though questions remain about the influence gender, ethnicity, and body morphometry have in the responses to this questionnaire. The aim of this study was to examine differences in ESS scores between various demographic groups of patients referred for polysomnography, and the relationship of these score to sleep-disordered breathing Methods:Nineteen hundred consecutive patients referred for polysom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
2
26
1
1
Order By: Relevance
“…The findings confirm the opinions of Hasselbacher et al that the ESS sensitivity is so low that the scale cannot be used as a screening tool when other clinical data is not provided [13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings confirm the opinions of Hasselbacher et al that the ESS sensitivity is so low that the scale cannot be used as a screening tool when other clinical data is not provided [13].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the ESS was found to show low sensitivity (53.2%) and specificity (58.8%) for diagnosis of moderate and severe OSAS (AHI ≥ 15/h). The similar results were reported by Hesselbacher et al for the American population; the ESS sensitivity for the diagnosis of the OSAS was 54% while its specificity 57% [13]. According to Hobson et al, the ESS sensitivity increased to 70% when items regarding driving a vehicle were excluded [14].…”
Section: Discussionsupporting
confidence: 81%
“…If necessary, other program faculty members are interviewed. At the same time, it is prudent to recognize that ethnic differences are known to impact the interpretation of the Epworth Scale and hence it is not a perfect test for assessment of alertness [8]. Ultimately, if fact-finding warrants, the trainee is referred to an internist for further assessment.…”
Section: Resultsmentioning
confidence: 99%
“…22,26 Pois, sabe-se que a ESE é afetada por inú-meros fatores, incluindo gênero, etnia e morfometria corporal, 29 o que torna o seu uso susceptível a erros.…”
Section: Discussionunclassified